Pains of Youth - Allen, Doug; Porter, Gerry (2011)
Colour Directed by Charlie Tomlinson. Featuring Colin Furlong, Sandy Gow, Meghan Greeley, Natalia Hennelly, Brad Hodder, Darryl Hopkins, Allison Kelly. Sound Design by George Robertson. Lighting Design by Jennifer Butler. Costume Design by Gina-Ra C2C Theatre